RANCANG BANGUN VERY LOW HEAD (VLH) TURBIN UNTUK PEMBANGKIT LISTRIK PADA SALURAN IRIGASI DARMASABA DESA KERU KECAMATAN NARMADA KABUPATEN LOMBOK BARAT PROVINSI NUSA TENGGARA BARAT - , IRWAN ARDITIAJAYA, Dr.Ir. Suhanan,DEA ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Indonesia's energy crisis in a matter of time. Our oil reserves were becoming depleted. If not found a new oil wells, Indonesia's oil reserves will run out in 12 years. Production cavacity of indonesian oil eight times higher than the the world's oil producing countries, like Saudi Arabia and Libya. With oil reserves of around 4 billion barrels, Indonesia oil produced an average of 1 million barrels per day (bpd). Hydro power potential in Indonesia is very large, but utilization level is very small. Based on data from Directorate General of Electricity and Energy in 2008 Potential utilization of micro-hydro in Indonesia only 459 MW, while the newly utilized only 84 MW. NTB province with an area of only 2 million hectares have the potentiatof 4143.6 kW hydro. The purpose of this study was to produce an appropriate design of mechanical components with the potential locations. And another one is to determine the relationship between variations in discharge and the power generated. The method used in this study is an experimental method . The turbine tested and then record the data results necessary for data processing. Very Low Head (VLH) Turbine is a Turbine designed for very low head (less than 2 m). Darmasaba Irrigation channels Keru Village is locationas where the turbine tested. This location has water discharge of 40 l / s and 0.8 m head. Based on this potential VLH turbine was designed and produced a design with a runner diameter of 195 mm, 77 mm hub diameter, shaft diameter 195 mm, blade angles at inlet and outlet (Î²1) 44.1 o and (Î²2) 37.9 o Turbine Specific speed is 370 (rpm, Hp, m). Conclusion of the research that power produced by turbin on flow of 20.48 l/s are 6.37 on 50 rpm, 21.13 watt on 70 and 21.56 watt on 100 rpm while at the maximum flow 34.5 l / s the power generated are 64.69 watt on 50 rpm, 84.52 watt on 70 rpm and 120.75 watt on 100 rpm. Based on the data obtained can be concluded that the turbines made produce maximum power at high speed. The maximum efficiency of the turbine (58%) occurs at 100 rpm and flow of23 l / s